A Study on the Appropriate Use of Magnetic Resonance Imaging (MRI) for Outpatients Referred to Hajar University Hospital in Shahrekord City, Iran, in Year 2017 - Niloufar Sadeghi; Mathias Hossain Aazami; Elham Raeisi; Kimia Hosseini; Mohamad-Ali Dayani; Niloufar Lalegani (مجله دانشکده پزشکی اصفهان, 2020)
Background: Magnetic resonance imaging (MRI) is a valuable diagnostic tool by its noninvasive/nonionizing nature. The aim of the current study was to determine the justification of MRI in outpatients referred to Hajar university hospital, In Shahrekord City, Iran, in a one-year period of 2017.